Social and Emotional Competencies among Saudi Female University EFL Students - Sara Fraih; Mona Sabir (Language Center of Islamic Institute of Uluwiyah, Mojokerto, Indonesia., 2025)
This study investigates the social-emotional competencies (SEC) of Saudi female students learning English as a Foreign Language (EFL), an underexplored dimension in higher education. Using the Social-Emotional Foreign Language Learning Scale (SEFLLS), data were collected from 63 students enrolled in a compulsory English course at a university in Jeddah. Findings revealed generally high SEC, with social relations strongest and self-regulation weakest. Open-ended responses complemented quantitative results. The study highlights the need to integrate social-emotional learning (SEL) into EFL instruction to enhance well-being and performance, aligning with Saudi Vision 2030’s goals for developing globally competent learners.